Breathable, durable and bark-shaped MXene/textiles for high-performance wearable pressure sensors, EMI shielding and heat physiotherapy - Zheng, Xianhong; Wang, Peng; Zhang, Xiansheng; Hu, Qiaole; Wang, Zongqian; Nie, Wenqi; Zou, Lihua; Li, Changlong; Han, Xu (Composites. Part A, Applied science and manufacturing, 2022)
[Display omitted] •Bark-shaped MXene/textiles (BMF) are fabricated via a scalable pad-drying strategy.•BMFs show good flexibility, air/vapor permeability and electrical conductivity.•The bark-shaped structure enhances the surface scattering of electromagnetic waves.•BMFs show excellent pressure sensing performance owing to the bark-shaped structure.•BMFs show remarkable joule heating performance. Flexible wearable electronics have attracted tremendous interest owing to their potential applications on artificial intelligence, electronic skin, human health monitoring, etc. However, it remains challenging to fabricate electronic textiles (E-textiles) without sacrificing the air/vapor breathability, flexibility and comfortability. To address these issues, we develop a novel surface reconstruction strategy through the facile and scalable pad-drying technology towards the breathable, flexible, highly conductive, bark-shaped MXene/textiles (BMFs). The formation mechanism of bark-shaped morphology is clarified in detail. Benefiting from synergistic effects between the bark-shaped MXene microstructure and porous structure of textiles, BMFs show excellent piezoresistive sensing performance and good electromagnetic interference (EMI) shielding performance. In addition, BMFs achieve remarkable joule heating performance of 146.7 °C at 5 V, which is even superior to the silver nanowire decorated fabrics. This work provides a new approach for the scalable fabrication of E-textiles, and lays the foundation for the next generation wearable electronics.